Dose-Dependent Effect of Hydrogen Sulfide in Cyclophosphamide-Induced Hepatotoxicity in Rats - Özatik, Fikriye Yasemin; Özatik, Orhan; Tekşen, Yasemin; Koçak, Havva; Arı, Neziha Senem; Çengelli Ünel, Çiğdem (Turkish Journal of Gastroenterology, 2023)
Background: Cyclophosphamide is a commonly used anticancer and immunosuppressive agent; however, hepatotoxicity is one of its severe toxicities. Hydrogen sulfide is a gaseous signaling molecule that plays crucial regulatory roles in various physiological functions. This study aimed to evaluate the hepatoprotective effect of hydrogen sulfide against cyclo phosp hamid e-ind uced hepatic damage in rats. Methods: Hepatotoxicity was induced by the single intraperitoneal administration of cyclophosphamide (200 mg/kg). Sprague–Dawley rats were treated by hydrogen sulfide donor, sodium hydrosulfide (25, 50, and 100 μmol/kg, intraperitoneal) 7 days before and 7 days after the administration of a single intraperitoneal injection of cyclophosphamide (200 mg/kg). Cyclo phosp hamide-ind uced hepatotoxicity was evaluated by serum and tissue biochemical and histopathological assessments. The levels of hydrogen sulfide, nitric oxide, cyclic guanosine monophosphate, interleukin 6, and interleukin 10 in liver homogenates were also determined by ELISA. One-way analysis of variance and Kruskal–Wallis tests were used as statistical analyses. Results: Cyclophosphamide increased liver function enzymes (alanine aminotransferase and aspartate aminotransferase), immunoreactivity to caspase-3 and Apaf-1, and proinflammatory cytokines. Cyclophosphamide also induced histopathological alterations including pycnotic nucleus with eosinophilic cytoplasm, increased sinusoidal dilatation, congestion, and edema. Hydrogen sulfide cotreatment significantly reduced cyclo phosp hamid e-ind uced inflammation, histological alterations, and apoptosis in the liver. 50 mg/kg sodium hydrosulfide was more effective against cyclo phosp hamid e-ind uced hepatotoxicity. Conclusion: In conclusion, hydrogen sulfide with its anti-inflammatory and anti-apoptotic effects seems to be beneficial as an adjunct to cyclophosphamide treatment to reduce cyclo phosp hamid e-ind uced hepatotoxicity and thereby can be suggested as a promising agent to increase the therapeutic efficacy of cyclophosphamide.